2020
DOI: 10.1002/admt.201901054
|View full text |Cite
|
Sign up to set email alerts
|

Paper Robotics: Self‐Folding, Gripping, and Locomotion

Abstract: a century, sensational engineering efforts have been performed to develop new synthetic materials, and intensive studies of forces needed to deform those soft materials have examined the use of pneumatic, thermal, electrical, and chemical energy. [11][12][13] The second research stream designs low-profile, sheet-like robots, named "robotic origamis" (or "robogamis") that offer softness and reconfigurability with multiple bending degrees of freedom. [8][9][10] In robogamis, the rigid sheets are connected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…For instance, Ryu et al reported an omega-shaped aquatic insect robot by using soft paper substrates and a water-responsive origami technique. [126] The device can float on the surface of water and be triggered by the sprayingevaporating cycles of water, then a forward locomotion with a theoretical speed of 10.9 mm s −1 was achieved.…”
Section: Biomimetic Robotsmentioning
confidence: 99%
“…For instance, Ryu et al reported an omega-shaped aquatic insect robot by using soft paper substrates and a water-responsive origami technique. [126] The device can float on the surface of water and be triggered by the sprayingevaporating cycles of water, then a forward locomotion with a theoretical speed of 10.9 mm s −1 was achieved.…”
Section: Biomimetic Robotsmentioning
confidence: 99%
“…As shown in Figure 5E, the multiple-base-shape creased kirigami structures are frequently related to self-folding [122,[124][125][126][127][128][129][130][131][132][133] and the concepts of 4D printing, which usually consists of several basic geometries adjacent to each other and would be "clutched" to a designed 3D structure through preprocessing [134] and external stimulation or guiding. [4,5] These structures have attracted large amounts of attention because they are easily designable, low-cost, less time-consuming for fabrication, have a low rate of waste production, and are suitable for volume production.…”
Section: Kirigami-inspired Applicationsmentioning
confidence: 99%
“…Scientists have developed different types of origami-inspired soft robots with a variety of materials and actuation methods, each with specific mechanical manipulation functions and movement styles 20 . For instance, a battery-free miniature origami robotic arm based on origami actuation was developed with shape memory alloys and has been used for arm orientation control and object grasping 21 .…”
Section: Introductionmentioning
confidence: 99%